IMPROVING COMMUNITY INSIGHT IN VILLAGE DEVELOPMENT PLANNING IN LEUMUKUTAN VILLAGE SEI RAYA BENGKAYANG REGENCY - M. Sabran Achyar; Arifin; Nurwijayanto; Laras Putri Olivia (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The fundamental problem in a village, including villages in Sungai Raya Kepulauan, especially on Lemukutan Island, is the issue of village development planning. This community service aims to engage in direct dialogue and strengthen a sense of togetherness by giving gifts to the community. The implementation method of this community service is direct dialogue to provide insight into village planning. The results of the community service show that there has been an increase in solidarity between the implementation team and the village community. This solidarity is reflected in the participatory interaction between the TeamTeam and the residents. This activity not only provides indirect insights to the village community but also fosters awareness and a spirit of cooperation among the community to take an active role in the development of their region.